Optimalisasi Fungsi Legislasi Anggota Dewan Perwakilan Rakyat Daerah Melalui Pemahaman tentang Metode Omnibus Law - Hartati; Ansorullah; Firmansyah Putra; Dinda Syufradian Putra; Dimas Subekti (Forum Kerjasama Pendidikan Tinggi, 2025)
The purpose of the Community Service Programme (PPM) is to find the concept of strengthening and regulating the function of Local Regulation Formation in the DPRD. The method used was in the form of lectures or presentations, demonstrations, and questions and answers. This method is used to deliver material in the form of legislation theory, apply the material, and provide opportunities for participants who still do not understand the material. The urgency of this PPM is by looking at the fact that legal products in the regions are not achieved according to the legislative target. Several new laws and regulations passed in several regions after the enactment of the Job Creation Law have been submitted for judicial review at the Constitutional Court. These are some of the problems with the Local Regulation Formation function. The weakness of the DPRD in carrying out the function of forming local regulations stems from the low level of initiative of DPRD members in the making of local regulations (legislative initation) and in the discussion of proposals for the formation of local regulations on the proposal of the DPRD (law making process). Optimal implementation of the legislative function of the DPRD must be supported by functional DPRD organs and a reliable supporting system as well as a blue print for strengthening the legislative function. The expected results are as follows: 1) repositioning the Council as a law centre. 2) strengthening the supporting system of the DPRD, 3) making a blue print for the legislative function of the DPRD.